Surgical Outcome of Ileal Pouch—Anal Anastomosis When Used Intentionally for Well-Defined Crohn’s Disease - Le, Quy (Inflamm Bowel Dis, 2013)
BACKGROUND: Crohn’s disease (CD) is considered a contraindication to ileal pouch—anal anastomosis (IPAA). In this study, we compare outcomes of CD and ulcerative colitis (UC) patients undergoing IPAA. METHODS: Patients were considered to have CD before surgery based on a history of small bowel disease, perianal disease, noncrypt-associated granuloma, or pretreatment skip colonic lesions. Patients were prospectively assessed for pouchitis or CD. Postoperative CD (pouch inflammation into the afferent limb or pouch fistula) or pouch failure (need for permanent diversion) were assessed. Preoperative serum was assayed for IBD-associated antibodies using enzyme-linked immunosorbent assay (ELISA). RESULTS: Seventeen patients with preoperative CD were identified. Seven (41%) patients developed postoperative recurrent CD in the afferent limb (n = 3) or pouch fistulizing disease (n = 4). One patient (6%) required pouch excision. The incidence of postoperative CD was higher (P = 0.002) in preoperative CD patients (41%) than UC patients (11%). There was no significant difference in pouchitis or pouch failure. There was also no significant difference in any preoperative clinical feature between patients with or without postoperative CD. Afferent limb inflammation developed in three (50%) of the six patients with pANCA+/OmpC− expression compared to none of the 11 patients without this serologic profile (P = 0.03). CONCLUSIONS: Although the intentional use of IPAA in CD has a higher incidence of postoperative disease vs. UC patients, there was no significant difference in pouch failure. Demographics, clinical features, and serologic factors do not predict outcome of CD patients undergoing IPAA. IBD serology may identify the phenotype manifestation of postoperative recurrent CD.